2021
DOI: 10.1038/s41467-021-24955-3
|View full text |Cite
|
Sign up to set email alerts
|

High-performance photonic transformers for DC voltage conversion

Abstract: Direct current (DC) converters play an essential role in electronic circuits. Conventional high-efficiency DC voltage converters, especially step-up type, rely on switching operation, where energy is periodically stored within and released from inductors and/or capacitors connected in a variety of circuit topologies. Since these energy storage components, especially inductors, are fundamentally difficult to scale down, miniaturization of switching converters proves challenging. Furthermore, the resulting switc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Optical conversion and transmission of power in semiconductors is what solar photovoltaics is all about, but it is also at the heart of many emerging fields of optics, including photonic power transfer, optical DC converters, and thermophotonics. [1][2][3][4] All of these fields are also strongly influenced by recent developments in thin-film device fabrication and processing. 5,6 As the device layers are thus being shrunk towards the wavelength of light and even beyond, one of the key questions is by how much one can one boost the overall optical conversion efficiencies by making use of near-field and optical cavity effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optical conversion and transmission of power in semiconductors is what solar photovoltaics is all about, but it is also at the heart of many emerging fields of optics, including photonic power transfer, optical DC converters, and thermophotonics. [1][2][3][4] All of these fields are also strongly influenced by recent developments in thin-film device fabrication and processing. 5,6 As the device layers are thus being shrunk towards the wavelength of light and even beyond, one of the key questions is by how much one can one boost the overall optical conversion efficiencies by making use of near-field and optical cavity effects.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report on our ongoing investigations around the questions brought up in the previous paragraph. We focus on two general topics: (1) extremely thin (∼ 10 nm) emitter and absorber layers enclosed in the same optical cavity, and (2) moderately thin (>100 nm) active layers as part of a device interacting with free space, in this case an ultra-thin solar cell. For topic (1), we study whether the overall electroluminescence (EL) of an extremely thin layer can be enhanced by placing it in an optical cavity together with an absorber layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the radiative heat transfer (RHT) between two bodies at subwavelength separation distances would diverge from the limit predicted by the Stefan–Boltzmann law . In contrast to far-field systems, the near-field RHT (NFRHT) enables a high-efficiency energy transport, which can be far ahead of the blackbody limit by several orders of magnitude, either theoretically or experimentally, via the resonant coupling of surface phonon polaritons (SPhPs) or surface plasmon polaritons (SPPs). The huge power density of near-field transport not only attracts particular scientific interest triggered by experimental advances but also benefits a series of potential applications, such as thermophotovoltaics, thermal logic circuitry, photon transformers, and photonic cooling . Since the huge heat flux is of critical importance in these applications, over the past decade, continuous efforts have been devoted to maximizing such RHT by controlling various material and structural parameters. Ordinarily, since the dominant contribution to heat transfer arises from polaritons modes, a natural idea for enhancement is to use an external stimulus to strengthen surface resonant modes of materials, such as electrochemical doping, , electrononreciprocity, tensile stress, and magnetic field. , For instance, Papadakis et al found that the accumulation of charge carriers enhances the SPP thermal channel of the metal–oxide–semiconductor capacitor and substantially increases the heat fluxes up to 225%.…”
Section: Introductionmentioning
confidence: 99%
“…1 In contrast to far-field systems, the near-field RHT (NFRHT) enables a highefficiency energy transport, which can be far ahead of the blackbody limit by several orders of magnitude, either theoretically or experimentally, via the resonant coupling of surface phonon polaritons (SPhPs) or surface plasmon polaritons (SPPs). 2−6 The huge power density of near-field transport not only attracts particular scientific interest triggered by experimental advances 7−12 but also benefits a series of potential applications, such as thermophotovoltaics, 13−15 thermal logic circuitry, 16−19 photon transformers, 20 and photonic cooling. 21 Since the huge heat flux is of critical importance in these applications, over the past decade, continuous efforts have been devoted to maximizing such RHT by controlling various material and structural parameters.…”
Section: ■ Introductionmentioning
confidence: 99%